Implementation of an emerging hospital-based violence intervention program: a multimethod study - Marcie Gawel; Christopher S Schenck; James Dodington; Lucero Paredes; Antwan Nedd; Pepe Vega; Kathleen M O’Neill (Trauma Surgery & Acute Care Open)
Background Individuals who experience assaultive firearm injury are at elevated risk for violent reinjury and multiple negative physical and psychological health outcomes. Hospital-based violence intervention programs (HVIPs) may improve patient outcomes through intensive, community-based case management.Methods We conducted a multimethod evaluation of an emerging HVIP at a large trauma center using the RE-AIM framework. We assessed recruitment, violent reinjury outcomes, and service provision from 2020 to 2022. Semistructured, qualitative interviews were performed with HVIP participants and program administrators to elicit experiences with HVIP services. Directed content analysis was used to generate and organize codes from the data. We also conducted clinician surveys to assess awareness and referral patterns.Results Of the 319 HVIP-eligible individuals who presented with non-fatal assaultive firearm injury, 39 individuals (12%) were enrolled in the HVIP. Inpatient admission was independently associated with HVIP enrollment (OR 2.6, 95% CI 1.3 to 5.2; p=0.01). Facilitators of Reach included engaging with credible messengers, personal relationships with HVIP program administrators, and encouragement from family to enroll. Fear of disclosure to police was cited as a key barrier to enrollment. For the Effectiveness domain, enrollment was not associated with reinjury (OR 0.70, 95% CI 0.16 to 3.1). Participants identified key areas of focus where needs were not met including housing and mental health. Limited awareness of HVIP services was a barrier to Adoption. Participants described strengths of Implementation, highlighting the deep relationships built between clients and administrators. For the long-term Maintenance of the program, both clinicians and HVIP clients reported that there is a need for HVIP services for individuals who experience violent injury.Conclusions Credible messengers facilitate engagement with potential participants, whereas concerns around police involvement is an important barrier. Inpatient admission provides an opportunity to engage patients and may facilitate recruitment. HVIPs may benefit from increased program intensity.Level of evidence IV.